Agricultural exposure and risk of soft tissue sarcomas and gastrointestinal stromal sarcoma in the AGRIculture and CANcer (AGRICAN) cohort. Issue 11 (29th January 2022) - Renier, Marine; Busson, Amandine; Boulanger, Mathilde; Piel, Clément; Pons, Romain; Tual, Séverine; Amadéo, Brice; Meryet‐Figuiere, Matthieu; Marcotullio, Elisabeth; Clin, Bénédicte; Baldi, Isabelle; Lebailly, Pierre; et al.
Abstract: Sarcomas are a heterogeneous group of tumors whose incidence is nearly 5 per 100 000 inhabitants in Europe. Their causes are poorly understood, although occupational exposures (especially farming and pesticides) are suspected. The AGRICAN cohort is a prospective study of 181 842 individuals enrolled in 2005 to 2007 who completed an enrolment questionnaire with data on lifelong agricultural exposure. Associations between agricultural exposure and sarcoma overall, gastrointestinal stromal tumors (GIST) and myomatous and fibrous sarcoma together, were analyzed with a Cox model. Until 2015, 188 incident cases of sarcoma were identified. Increased risks were observed (a) among cattle farmers working <10 years (HR<10years = 2.45, 95% CI 1.36‐4.43) and breeding ≥50 livestock (HR≥50animals = 3.84, 95% CI 1.60‐9.22), especially if involved in animal care and building disinfection, (b) in greenhouse production (HR = 1.82, 95% CI 1.01‐3.30) and (c) in field‐grown vegetable production (HR = 1.49, 95% CI 0.96‐2.32). Concerning histological subtypes, GIST were positively associated with pesticide use in vineyards (HR = 2.24, 95% CI 0.95‐5.30). For myomatous and fibrous sarcoma, the only increase was seen in field‐grown vegetable production (HR = 2.37, 95% CI 1.16‐4.85). In AGRICAN, the risk of sarcomas was increased in several farming activities with differences according to histological subtype. Abstract : What's new? While sarcoma risk is potentially influenced by agricultural exposures, relationships between sarcoma and factors such as pesticide exposure, livestock farming and occupational history of farming remain poorly understood. Here, data from the prospective AGRIculture and CANcer (AGRICAN) cohort in France reveals an increased risk of soft‐tissue sarcoma among cattle farmers, pig farmers and farmers working in greenhouses or raising field‐grown vegetables. Associations were notable for cattle farmers who were raising 50 or more animals, had close animal contact or were involved in building disinfection. Specific exposures were identified for several sarcoma subtypes, including elevated myosarcoma/fibrosarcoma risk among field vegetable growers.